Republic of Korea : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2019)
This Selected Issues paper analyzes monetary policy and financial cycles; the evolution of macroprudential policies in Korea; the efficacy in prudential policies in taming financial excess and building financial resilience and; the interaction between monetary policy and macroprudential policies. Evidence for Korea suggests that financial stability will not necessarily materialize as a natural by-product of a so-called appropriate monetary policy stance. Although the effects of monetary and macroprudential instruments may overlap, they are not perfect substitutes. Macroprudential policies can also impact the banking system by affecting bank funding costs through the net interest margin. In certain circumstances borrower-based prudential measures and monetary policy can complement one another. Macroprudential policies can impact banks profitability. Policymakers should be mindful that macroprudential policy is not free of costs and that there may be trade-offs between the stability and the efficiency of financial systems.